Informal Social Interactions, Academic Achievement and Behaviour: Evidence from Peers on the School Bus - Matthew A. Lenard; Mikko Silliman (CESifo GmbH, 2024)
We study the effects of informal social interactions on academic achievement and behaviour using idiosyncratic variation in peer groups stemming from changes in bus routes across elementary, middle, and high school. Our results suggest that student interactions outside the classroom—especially in adolescence—may be an important factor in the education production function for both academic and, particularly, behavioral skills. The effects of interactions on the bus are also related to neighborhood measures—suggesting that one way that interactions on the bus may matter is by amplifying interactions in the neighborhood.
Keywords: I21; C31; 330; social interactions; peer effects; education; behavior